Typical site seismic response analysis with reinforcement under earthquake and rainfall in the mountainous areas of China - Zhang, Jian; Cao, Licong; Shen, Hao (Frontiers in Earth Science, 2022)
Multi-tilted layered soil is widespread in the mountainous areas of China, and pile systems are widely applied to foundation support and repair. In order to investigate the seismic response of piles system in multi-tilted layered soils under earthquake and rainfall, two models were built and tested through a large 1-g shaking table. The interlayer is tilted and highly weathered, and it is saturated during rainfall. The piles are embedded in the bedrock with different lengths. The results showed that: (1) The acceleration response was weakened in the interlayer, and it diminished as the earthquake amplitude increased. The structures showed the maximum acceleration response. (2) The existence of water in the tilted interlayer led to a greater response of the superstructure. The bending moment of piles varied under different containers, which was mainly due to the inertial force of the container and the potential sliding force of the covering layer. The water in the interlayer from rainfall promoted the bending moment caused by the potential sliding force, increasing the potential risk of instability of the system. (3) The motion mode of the container under rainfall was translation. The rotation angle of the container with saturated moisture content would be significant and it increased with the increase of the earthquake amplitude.